(untitled) (Ricos Biology, 2025)
Hepatocellular carcinoma (HCC) remains the predominant cause of cancer-related mortality. Traditional diagnostic methodologies are invasive and exhibit limited sensitivity for early detection. Non-invasive alternatives, particularly liquid biopsies utilizing extracellular vesicles (EVs), have emerged as promising approaches. EVs contain crucial biomarkers, including mRNA, proteins, and nucleic acids. However, the limited abundance of EV mRNA in liquid biopsies has impeded its clinical application. To address this limitation, researchers have developed the Self-amplified and CRISPR-aided Operation to Profile EVs (SCOPE) platform. This innovative system integrates CRISPR-Cas13 for RNA target identification with replication and signal amplification, achieving subattomolar detection sensitivity. SCOPE offers high specificity with single-nucleotide resolution in a single-step assay. Investigators have validated probes targeting key mutations in KRAS, BRAF, EGFR, and IDH1 genes and developed an automated device for multi-sample analysis. SCOPE has demonstrated efficacy in identifying early-stage lung cancer in animal models, monitoring tumor mutational burden in colorectal cancer, and classifying glioblastoma patients. In HCC, EV mRNA exhibits potential for non-invasive detection of recurrence and monitoring disease progression. Current studies indicate that EV-based mRNA profiling holds significant promise for early detection, treatment monitoring, and recurrence prediction in HCC, offering valuable clinical applications. The integration of advanced platforms such as SCOPE with EV analysis could transform liquid biopsies in oncology, providing a rapid, highly sensitive, and non-invasive method for cancer detection and management.